The development of Complex Emergent Modularity: A reply to Favela, Amon, & van Rooij (2018). (August 2018) - Wastell, Colin A.; Purcell, Zoe; Howarth, Stephanie; Paterson, Wendy; Slocombe, Bianca
In our reply to Favela, Amon, & van Rooij (2018) we note points of agreement such as the necessity for the interaction between components in a system for it to be complex emergent and that the Dual Processes approach to human thinking has limitations. We also discuss several critical points of disagreement with the paper. We assert that Complex Emergent Modularity (CEM) does not proliferate the interaction problem but instead proposes a solution to the problem based on the contribution of the global workspace and the process of global broadcast. The nature of the entities which interact is described and emphasized as central to CEM theory.